(untitled) (Global Journal of Management and Business Research, 2020)
This study aims to study the Earnings management in light of the shift to International Financial Reporting Standards (IFRS) through a field study, which has occurred in Saudi jointstock companies. Through research, I achieved several results, such as: That there is change expected to happen in Earnings management in light of the shift to International Financial Reporting Standards (IFRS) via: Manipulating both the expenditure and revenue in the income statement, The manipulation of the accounts of Balance Sheet Statement, The manipulation of cash flows statement, as well as through the manipulation of reports of the changes in equity statement. The accountants in Saudi Corporations are concerned to shift to IFRS, expecting that the Earnings management is going on; thus, the IFRS had implemented.